Development of Network Agnostic SIM Technologies for M2M Data transfer (Vallis Aurea, 2019)
The development of smart devices and their functionality is not possible without adequate network connectivity.Every two to three years, smart devices increase their processing power, amount of memory and functionality for double. One of the limiting factors in the process of creating new smart devices is the way they connect to the network.Network connectivity must be reliable, inexpensive and financially affordable. Also, the device must be ready for manufacturing without additional costs. Many wireless networking technologies now exist on the market, but LPWAN and UICC are essential for the development of IoT devices in the next few years.